The idea of society: the Spoken World Theory and the ontological conceptualization of society - Van Langenhove, Luk (Frontiers in Sociology, 2023)
This article presents a new conceptualization of society with the ambition to sharpen thinking about social reality and to better understand how society relates to personhood. This exercise is framed in an attempt to develop the Spoken World Theory, inspired by the thinking of Rom Harré. It involves a radical rethink of the social ontology and is to be seen as an alternative to the traditional conceptualization of society as a social structure that is opposed to individual agency. The proposed alternative is based upon the disentanglement of four aspects of society along the Vygotskian public/private and individual/collective axes. As such, society can be said to manifest itself in four realms: (i) the world as we hear it: a worldwide and history-long ongoing web of conversations; (ii) the world as we see it: a set of materialized social artifacts, including a set of institutional facts; (iii) the world as we imagine it: individual umwelts or worldviews for each person based on appropriated knowledge and moral frameworks; and (iv) the world as we shape it: persons have the power to formulate intentions that they can bring to the conversational space or the space of artifacts. A major consequence of this conceptualization is that it no longer puts society outside human beings, nor that personality is only to be located inside persons. The proposed ontological framework allows us to speak in much clearer terms about how persons and society are entangled with each other in the sense that without the personhood of people, there can be no society, and that without society, people cannot have personhood. Both personhood and society are to be seen as two intertwined mechanisms that allow the individuals of the human species to complement the genetic basis of survival with a system of cultural resources that can be used for coping with everyday life. The article ends with a discussion of the practical implications of social theorizing.